The Red Zone: Why Beijing’s Air Pollution Crisis is More Complicated than You Think - Schipani, Samantha (Consilience, 2014)
Beijing’s air pollution crisis is immediately pressing, but multivariate analysis of the urban area reveal how complicated the issue is environmentally and economically.